PENGARUH KUANTITAS SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI - Wibowo, Pascalis Danny Kristi; Mandacan, Ebsan Hezron; Firlana, Habbi (Polteknik Imigrasi, 2024)
Abstract (In English). This research aims to obtain empirical evidence on the factors that influence the Quantity of Human Resources on Employee Performance at the Class I Non TPI Manokwari Immigration Office. As times progress, human resources will be required to be able to do everything, especially in the public service environment. There are many service activities in this office and the lack of personnel working at the Class I Non TPI Manokwari Immigration Office is the reason why this research was carried out. The object of this research is the Class I Non TPI Manokwari immigration office and the ranks of support offices under it such as the Passport Service Unit, Public Service Mall. The data used in this research is primary data using a questionnaire distribution technique aimed at respondents, namely employees of the Class I Non TPI Manokwari Immigration Office. The sample used in this research was 38 respondents. The data analysis technique used in this research was simple regression analysis using the SPSS test tool. The results of this research confirm the hypothesis formed. Quantity of Human Resources has a significant effect on 80,5% employee performance at the Class I Non TPI Manokwari Immigration Office.